DISCRIMINATION AND SYMPTOMS OF DEPRESSION IN PREGNANCY AMONG AFRICAN AMERICAN AND WHITE WOMEN - Canady, Renée B. (2008)
PURPOSE: Depressive symptomatology during pregnancy has been associated with negative health outcomes for both the mother and child. This study examines the potential associations between depression and depressive symptoms in poor women and African-American women and their lifelong experiences of discrimination. METHODS: Data from 2,731 African-American and White participants in the Pregnancy Outcomes and Community Health (POUCH) Study were analyzed. Multiple regression analyses were used to investigate relations between depressive symptoms and total discrimination, and between depressive symptoms and three discrimination types (gender, race, and socioeconomic). MAIN FINDINGS: Initial results showed that African-American women had greater levels of depressive symptoms than White women. Self-reported total discrimination and discrimination types were each positively associated with depressive symptomatology in all women. After adjusting for sociodemographic characteristics (maternal age, education, employment status, partner status, and Medicaid status) and examining significant interactions, the race difference in depressive symptomatology was evident only in employed women. The addition of total discrimination to the multi-covariate model eliminated race differences in the adjusted mean level of depressive symptoms. When the three discrimination types were modeled simultaneously with all other covariates, only gender and economic discrimination remained positively associated with depressive symptoms in African-American and White women. CONCLUSIONS: These results should be cautiously interpreted due to: 1) the study design; i.e., ascertainment of maternal discrimination and depressive symptoms at a single time point; and 2) limitations of the discrimination measure. Despite these limitations, the study points to potential links between lifetime discrimination and depressive symptoms in pregnancy.